International Interdisciplinary Consensus Meeting on the Evaluation of Developmental Dysplasia of the Hip - O’Beirne, Joseph Gerard; Chlapoutakis, Konstantinos; Alshryda, Sattar; Aydingoz, Ustun; Baumann, Thomas; Casini, Carolina; de Pellegrin, Maurizio; Domos, Gyula; Dubs, Beat; Hemmadi, Sandeep; Karantanas, Apostolos; Kolovos, Stylianos; Kraus, Tanja; Zhao, Liang; Maizen, Claudia; Mehdizadeh, Mehrzad; Molitorisz, Daniel; Persaud, Thara; Petratos, Dimitrios; Placzek, Richard; Placzek, Sonja; Scott, Sally; Schmid, Raoul; Tarrant, Ailbhe; Voulgaris, Konstantinos (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
In September 2018, an international meeting of doctors of various disciplines, with expertise in the detection and treatment of DDH, was held in Csolyospalos, Hungary. The aim was to achieve consensus on the detection and early treatment of the condition and to develop a standardized system of teaching and training for hip ultrasound. There was strong agreement that US screening is essential. Specifically the Graf technique was selected as the technique of choice. Universal US screening was strongly favored. Screening should be carried out as soon as possible, but not later than the sixth week of age. US screening is cost-effective, does not result in overtreatment, and contributes to a reduction of long-term consequences. The essential principle of treatment is timely application of a device to achieve reduction, retention and maturation, by holding the hips in flexion, and a safe degree of abduction. It was agreed that the effectiveness of any screening policy depends on the correct scanning technique. Therefore, standardization of teaching and training of the Graf technique is mandatory. A unified teaching policy and materials should be developed for this purpose. Certification, re-certification and audit were discussed. The group, which has been formalized as the International Interdisciplinary Consensus Committee On DDH Evaluation (ICODE), will continue to meet and work towards establishing international consensus on DDH, standardizing and developing teaching and training of the Graf technique for hip US, and maintaining standards for detection and management.
Keywords: education; training; quality assurance; musculoskeletal system; pediatrics